Managing Macadamia Decline: A Review and Proposed Biological Control Strategies - Xiaofang Yao; Qiumei Liu; Yongxin Liu; Dejun Li (Agronomy, 2024)
Macadamia decline poses a serious economic threat to the macadamia industry. It exhibits either a slow decline due to infection by Kretzschmaria clavus or Ganoderma lucidum, or a quick decline caused by pathogens like Phytophthora spp., Lasiodiplodia spp., Neofusiccocum spp., Nectria rugulosa, Xylaria arbuscula, Phellinus gilvus, Acremonium recifei, and Rosellinia spp. Chemical strategies, resistant cultivars, and agronomic measures have been widely adopted to control macadamia decline, but effective biological control measures have rarely been applied. This paper proposes two key steps for implementing biological control strategies, i.e., the isolation and selection of biological control agents from healthy plants, or from the disease-suppressive soil for the construction of synthetic microbial communities, and the integration of synthetic microbial communities with various strategies, including seed coating, root dipping, seedling substrate, soil drenching, foliar spraying, and application as a bio-organic fertilizer. By adopting these strategies, we aim to provide proactive and efficient approaches for combating macadamia decline and safeguarding the health of macadamia orchards.